Reproducibility of hemispheric lateralization over several days using functional transcranial Doppler sonography (fTCD): a pilot single-case study of word fluency - Florian Heimann; Sabine Weiss; Horst M. Müller (Journal of Integrative Neuroscience, 2022)
Functional transcranial Doppler sonography (fTCD) is a time- and cost-effective, non-invasive approach to determining real time hemispheric lateralization and is well-suited for repetitive study designs comprising multiple days. To date, no study has examined the reproducibility of the direction and degree (strength) of lateralization during word fluency (WF) over multiple, consecutive sessions within a single person, although there are many studies of lateralization during language processing. Moreover, there is conflicting evidence as to whether there is a relationship between the degree of laterality and the word fluency performance. In this study, one right-handed male (aged 24 years) completed a total of seven examination sessions in the time span of 10 days. Each session comprised multiple phonological and semantic WF tasks. The maximum difference of relative cerebral blood flow velocity (CBFV) changes between the left and right middle cerebral artery (MCA) during WF was defined as the Lateralization Index (LI). The word-fluency performance and the LIs were used in a linear regression model to detect relative changes in the direction and degree of lateralization during repetitive WF tasks. The reproducibility of the direction of language-related lateralization is very stable over multiple sessions within this single person and the processed LIs were left-lateralized in every session for both WF tasks. In addition, performance during phonological WF could significantly predict the variability in the degree of lateralization. This result could not be confirmed for the semantic WF task. The results of this pilot study support the usage of fTCD as a reliable method for examining lateralization patterns, especially in longitudinal study designs. They also provide evidence for the notion that performance in WF tasks can be related to the degree of lateralization, at least intra-individually.